Functus Officio: Sempadan "Terpakai" dan "Tidak Terpakai" (Kanun: Jurnal Undang-undang Malaysia, 2013)
One of the most important aspects in legal management is related to "decision". Decision will lead the mission in matters related to actions to be taken, including in deciding appeal. This article discusses the finality of a decision which leads to a paramount discussion, that is "functus officio". For that purpose, this article will discuss the "functus officio" aspect from its concept, application (including its application in specific areas), implication, and its exceptions.Keywords: functus officio, decision, adopted, not adopted